Cilliní: (Re)addressing the past in the present. Issue 1 (1st December 2020) - Allen, Victoria; Duffy, Joe; Scally, Garret
This article examines the 'Cilliní' project's interdisciplinary approach of research and filmmaking practice to explore the phenomena of Cilliní. The project has created artwork that investigates and visualizes landscapes and provides a spatial narrative on the subject of Cilliní, which were historic sites in Ireland used for the burial of 'unfortunates', principally stillborn and unbaptized infants. The article draws on the material created and experiences involved in making the short film The Lament and creating a virtual reality installation, Cilliní Tales, which, respectively, employ the technologies and approaches of drone and 360° camera filmmaking. As the article combines the perspectives of digital storytelling, cultural memory and a consideration of the ethics of undertaking such a project, it is written in the form of a triptych. This article addresses how the (re)visitings and difficult enquiries of arts-based research in the 'Cilliní' project contribute to an ongoing social, political and ethical reappraisal of Cilliní and the implications of (re)addressing the past in the present.